THE DEVELOPMENT OF QUALITY MANAGEMENT STRATEGY TO SENIOR HIGH SCHOOL (A Case Study at Some Public Senior High Schools and Vocational High School in Bandung City) - Masyhur, Hadi (International Journal of Education, 2010)
This study aimed at developing a strategy of quality management of senior high schools in Bandung City through education services satisfying students. Qualitative and quantitative methods were used. Results of the study showed first satisfaction index score of secondary education service in Bandung City was 1.74 (unsatisfactory). Second Quality management strategy developed through five strategic elements covering arena, vehicle, differentiation, stage and economic logic. Third, Balanced Scorecard mapped the strategy result through four perspective comprising learning and growth, internal process, customer, and financial. The study suggested several recommendations. First to assure teachers’ competencies, system of quality management needs to be developed with quality standard and use of Information and Communication Technology (ICT) in order to add learning resources for teachers and students, besides, school management will be able to conduct partnership and networking for continuous quality improvement. Second policy concerning with development of blue print for quality improvement of senior high schools in Bandung need to be issued. Third performance contract between headmaster and Bandung board of education in dealing with fulfillment of the blue print based on key performance indicators need to be organized. Fourth Quality Award Program for achievement of secondary education quality that will make school proud and create new conducive climate for secondary school need to be arranged.